Effect of cover crops residues on crambe cultivation (2018)
Although the crambe is commercially exploited in Brazil, there is a demand for studies that allow the improvement of the techniques involved in its cultivation. Planting on residues of different species can provide greater vegetative and reproductive development. Thus, the objective of this work was to evaluate the vegetative and reproductive development of crambe cultivated on residue of different species, in succession to the cultivation of lettuce. The experimental design was a randomized block design, with six treatments containing the following cover crops residues: crotalaria (Crotalaria juncea), pigeon pea (Cajanus cajan), porcine bean (Canavalia ensiformis), millet (Pennisetum glaucum) and sorghum (Sorghum bicolor), besides a control treatment, with the use of spontaneous vegetation. At 49 days the vegetative development was evaluated by measuring plant height, stem diameter at the soil level, number of leaves, relative content of leaf chlorophyll, number of lateral branches, fresh and dry biomass of shoot. The productive variables were evaluated at 95 days after planting, obtaining the grain mass per plant, the hectoliter weight of the grains and estimating the productivity of each treatment, as well as its gross revenue. It was verified that the maintenance of residue of cover crops benefits the vegetative development of the crambe crop, without statistically altering grain yield. However, this technique results in an economic benefit, with the increase in gross revenue, being recommended during the fallow, to the detriment of the management of spontaneous plants.